Adoption of mobile data services in Singapore : a needs-based perspective - Ang, Kai Ling (2008)
Mobile Data Services are an emerging phenomenon in Singapore. We used 3-stage exploratory research comprising surveys, focus groups and weblog analysis to capture the emerging phenomenon because MDS is not established in Singapore. Beginning with a macro-level perspective, we explored the success of the Mobile Data Services (MDS) industry in Japan, in particular i-mode followed by the attractiveness of Singapore as a viable telecommunications market. Next, we discuss our research findings, which suggest that MDS firms should pay particular attention to cognitive needs and business uses in their promotional campaigns before outlining some of the emerging trends in the MDS industry. We conclude by making recommendations for a hypothetical MDS market player based on our research, which will ideally stimulate adoption of MDS in Singapore.